Aquisição e retenção de clientes sob a perspectiva do marketing de relacionamento - Oliveira, Leandro Sanchez de (2006)
Over the last years, it has been noticed a growing concern about customer retention. Boosted by Marketing Relationship concepts, maintenance and development initiatives has spread through the companies budgets, starting to compete with traditional efforts of acquisition and transaction marketing. In spite of the competitive scenario of some companies demands a strategy focused on retention, the need of customer acquisition won t never vanish and the organization reality doesn t always reflect the two approaches (acquisition and retention) living together in a harmonic way. What should happen is an alignment between both strategies to make marketing efforts more efficient and provide the company with the maximum return possible from its relationships. In this context, an exploratory research was made, using case study methodological procedure, in order to analyze how acquisition and retention initiatives are practiced in the Relatioship Marketing. As a research unit, Vivo, the biggest mobile carrier in the brazilian market, was used to illustrate that reality. This work has showed that the researched company is in the middle of a transition, adjusting its strategy with the market moment. The focus on quality (looking forward to retention) and selected acquisition is a sign of an structured evolution, aligning its marketing strategy consistently, and aiming business rentability. Despite the tactic-operational changing rhythm doesn t correspond to marketing and some internal expectations, the company demonstrated to be developing consistents initiatives, lacking a bit of speed eventually. For that, it has many updated concepts and tools to guide its business under a relationship perspective. It s worth to point out that the finds and conclusion of this research can t be applied to other case without the proper analysis of peculiarities of companies and industry and identification of the moment in which they are. This dissertation contributed to a broader view of Relationship Marketing theory, reducing the myopia caused by the excessive appreciation of retention initiatives, assisting the elaboration of new hypothesis and instigating futures studies about the importance of not only the maintenance but also the acquisition activities and their alignment.